Cold Thermal Priming of Laminaria digitata (Laminariales, Phaeophyceae) Gametophytes Enhances Gametogenesis and Thermal Performance of Sporophytes - Gauci, Clément; Bartsch, Inka; Martins, Neusa; Liesner, Daniel (Frontiers in Marine Science, 2022)
Thermal characteristics of kelp species have been studied in many ways, but potentially persistent effects of temperature across generations are yet poorly understood. In this context, the effect of thermal priming on fertility and growth of the N-Atlantic kelp species Laminaria digitata was investigated within and across life cycle generations in a two-step common garden experiment. Using vegetative clonal gametophytes from cold (5°C) and warm (15°C) pre-experimental cultivation (3 years), we first quantified gametogenesis and recruitment over two weeks at a common temperature of 10°C. Then, recruited sporophytes were transferred to a temperature gradient spanning the tolerance range of the species from 0°C to 20°C. We hypothesized that a warm gametophyte pre-experimental cultivation promotes performance of sporophytes at warm temperatures and vice versa. Interestingly, gametogenesis speed and sporophyte recruitment were higher in gametophytes following cold compared to warm pre-experimental cultivation, which indicates carry-over effects of temperature within the gametophyte generation. Compared to warm pre-experimental cultivation of gametophytes, a cold pre-experimental cultivation enhanced growth of juvenile Laminaria digitata sporophytes by more than 69% at the extreme low and high temperatures of 0 and 20°C. This is the first evidence for a cross-generational effect between gametophyte parents and offspring sporophytes. As cold gametophyte cultivation increased the trait performance of gametogenesis, recruitment and thermal tolerance of juvenile sporophytes, priming of early life cycle stages may be used to increase resilience and productivity of kelps in marine forest restoration efforts and kelp mariculture.